2015
DOI: 10.1002/jcph.442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uptake transporters OAT3 and OATP1B1 and efflux transporter MRP2 on the pharmacokinetics of eluxadoline

Abstract: The effects of OATP1B1, OAT3, and MRP2 on the pharmacokinetics of eluxadoline, an oral, locally active, opioid receptor agonist/antagonist being developed for treatment of IBS-d were assessed in vivo. Coadministration of a single 200 mg dose of eluxadoline with cyclosporine, and probenecid increased eluxadoline systemic exposure [AUC(0–inf)] by 4.4- and 1.4-fold, respectively, whereas peak exposure (Cmax) increased 6.2-fold and 1.3-fold, respectively. Cyclosporine had little effect on renal clearance (CLren) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 25 publications
2
63
1
Order By: Relevance
“…The mechanism of these changes has not yet been fully worked out. It is worth noting that the clinical relevance of MRP2 inhibition DDI is minimal in humans, with exposure levels reaching 121%-234% of those in normal subjects, depending on the drug considered (Chester et al, 2003;Suwannakul et al, 2008;Ieiri et al, 2009;Brennan et al, 2015;Davenport et al, 2015). Recently, the specificity of CPs I and III transport was studied using cells transfected with various transporters (Bednarczyk and Boiselle, 2016).…”
Section: Coproporphyrin As Endogenous In Vivo Probe For Oatp1bmentioning
confidence: 99%
“…The mechanism of these changes has not yet been fully worked out. It is worth noting that the clinical relevance of MRP2 inhibition DDI is minimal in humans, with exposure levels reaching 121%-234% of those in normal subjects, depending on the drug considered (Chester et al, 2003;Suwannakul et al, 2008;Ieiri et al, 2009;Brennan et al, 2015;Davenport et al, 2015). Recently, the specificity of CPs I and III transport was studied using cells transfected with various transporters (Bednarczyk and Boiselle, 2016).…”
Section: Coproporphyrin As Endogenous In Vivo Probe For Oatp1bmentioning
confidence: 99%
“…Animal studies demonstrated that eluxadoline interacts with opioid receptors in the gut to reduce intestinal contractility and inhibit neurogenically mediated secretion, while normalizing stress-induced acceleration of upper GI transit, without rebound constipation [13,14]. The activity at the d-opioid receptor ameliorated the anti-transit effects of the l-opioid receptor activity [14].…”
Section: Pharmacodynamicsmentioning
confidence: 98%
“…Plasma protein binding of eluxadoline was 81 % [5]. The mechanism of eluxadoline metabolism is currently unclear; however, some evidence exists pointing to limited glucuronidation leading to the formation of an acyl glucuronide metabolite, detectable in urine [5,13]. Eluxadoline is mostly (82 %) excreted in feces; \1 % was found in the urine.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations